2017
DOI: 10.1515/polyeng-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the properties of maleated poly(lactic acid) and its effect on poly(lactic acid)/cellulose nanofiber composites

Abstract: AbstractIn this research, maleated poly(lactic acid) (PLA-g-MA) was manufactured by different levels of maleic anhydride (MAH). Also PLA-g-MA effects as a compatibilizer were investigated on PLA/cellulose nanofiber (CNF) composites. The grafting reaction was performed in the presence of dicumyl peroxide (DCP) as an initiator at constant level (0.2 phr) via reactive extrusion. Furthermore, the effects of four different levels of MAH (1–4 phr) were studied on the physical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Nevertheless, the results obtained for the compatibility of various PLA-based blends are significant. Examples of variations in mechanical properties are shown in Table 2 in blends of PLA/cellulose nanofibers (CNF) [24].…”
Section: Direct Functionalization Of Pla Backbone: Towards Pla-based ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the results obtained for the compatibility of various PLA-based blends are significant. Examples of variations in mechanical properties are shown in Table 2 in blends of PLA/cellulose nanofibers (CNF) [24].…”
Section: Direct Functionalization Of Pla Backbone: Towards Pla-based ...mentioning
confidence: 99%
“…Nevertheless, the results obtained for the compatibility of various PLA-based blends are significant. Examples of variations in mechanical properties are shown in Table 2 in blends of PLA/cellulose nanofibers (CNF) [24]. The following paragraphs show the main PLA graft copolymers obtained from PLA-g-MA with their principal properties and applications.…”
Section: Pla-g-maleic Anhydride (Pla-g-ma)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although CNF has gained substantial market interest as an alternative to inorganic nano-sized reinforcements in nanocomposite materials, the main challenge of using nanofiber is the difficulties of achieving good nanofiber dispersion in a non-polar medium due to their polar surfaces [ 35 ]. CNF has been shown to be compatible with PLA based on previous studies, but agglomeration was observed to occur at a certain amount of CNF, notably at higher loading.…”
Section: Introductionmentioning
confidence: 99%